Intraspecific Variation of Biological Activities in Venoms from Wild and Captive Bothrops jararaca - Saad, Eduardo [UNESP]; Barros, Luciana Curtolo [UNESP]; Biscola, Natalia [UNESP]; Pimenta, Daniel Carvalho [UNESP]; Barraviera, Silvia Regina Catharino Sartori [UNESP]; Barraviera, Benedito [UNESP]; Ferreira, Rui Seabra [UNESP] (Taylor & Francis Inc, 2012)
The venom of Bothrops jararaca is composed of complex mixture of molecules, mainly lectins, metalloproteinases, serinoproteinases, desintegrins, phospholipases, and peptides. This composition may vary according to the snake's age, gender, and region of origin. The aim of the was to determine individual variation in Bothrops jararaca venom in the Botucatu region, São Paulo State, Brazil, by means of enzymatic, biochemical, and pharmacological characterization, utilizing in vitro tests and biological assays. The activities were compared with those of Brazilian Reference Venom (BRV). Protein concentration varied between adult and juvenile groups. The electrophoretic profiles were similar, with molecular masses ranging between 25 and 50 kD, but with intraspecific variations. Reverse-phase high-performance liquid chromatography (RP-HPLC) revealed protein concentration differences. Coagulant activity did not differ significantly among adult groups, but there was a large variation between juvenile venom and BRV, which coagulated more extensively. Venoms from adults displayed greater hemorrhagic activity, especially in males recently obtained from the wild. In contrast, juveniles kept in captivity and adult males showed higher values. Edematogenic activity displayed an increase in edema in all groups. At the mean lethal dose (LD50), toxicity varied significantly between groups, with venom from captive females being threefold more toxic than juvenile venom. Data illustrate the intra-and interspecific complexity that occurs in snake venoms, which may be attributed to ontogenetic, sexual, and environmental factors that affect variability in Bothrops jararaca venom. Further, it is proposed that Brazilian public health authorities document the constitution of pooled venom employed in the immunization of serum-producing animals due to this variability in venom properties. Given the large Brazilian territory, this variability requires regional monitoring and evaluation of the efficacy of bothropic antivenom in treatment of snakebite and consequent permanent sequelae observed.